Design for a Modular Clinical Trial Recruitment Support System Based on FHIR and OMOP - Reinecke, Ines; Gulden, Christian; Kümmel, Michéle; Nassirian, Azadeh; Blasini, Romina; Sedlmayr, Martin (Digital Personalized Health and Medicine, 2020)
The MIRACUM consortium is developing a Clinical Trials Recruitment Support System to support the data-driven recruitment of patients for clinical trials. The design of the prototype includes both open source solutions (OMOP CDM, Atlas) and open standards for interoperability (FHIR). The aim of the prototype is to create a patient screening list of potential participants for a clinical study. The paper shows the modular structure and functionality of the prototype building the foundation for the practical implementation of the CTRSS and, at the same time, demonstrating the use of open source solutions and standards for the development of clinical support systems.
CRIS-Team Scopus Importer:2020-07-03
Keywords: automation; clinical trial recruitment support system; decision support systems; FHIR; OHDSI; OMOP; open standards; secondary use of electronic health records